Policy uncertainty and the sequence of entry by Japanese firms, 1980–1998 - Delios, A; Henisz, W J (Journal of International Business Studies, 2003)
We extend the stages model of internationalization to incorporate a sophisticated consideration of temporal and cross-national variation in the uncertainty of the policy environment. Using a sample of 6465 international expansions of 665 Japanese manufacturing firms in 49 countries, we develop arguments from internationalization and bargaining power perspectives to show how Japanese firms manage policy uncertainty in host country environments through the within-country sequencing of investments. Although a distribution to manufacturing entry sequence tends to prevail in countries with low levels of policy uncertainty, as uncertainty in the policy environment increases, initial entry by distribution is increasingly likely to be eschewed in favor of an initial entry by a joint venture manufacturing plant. We suggest that this change in investment sequence occurs as firms shift from an emphasis on developing knowledge about local markets and consumers in low-hazards markets to an international expansion strategy in uncertain policy environments that places knowledge development of the policy environment at the forefront of a firm's strategy.